Activity Performance, Participation, and Quality of Life Among Adults in the Chronic Stage After Acquired Brain Injury—The Feasibility of an Occupation-Based Telerehabilitation Intervention - Beit Yosef, Aviva; Jacobs, Jeremy M.; Shenkar, Shira; Shames, Jeffrey; Schwartz, Isabella; Doryon, Yehudit; Naveh, Yuval; Khalailh, Fatena; Berrous, Shani; Gilboa, Yafit (Frontiers in Neurology, 2019)
Objective: Acquired brain injury (ABI) is a leading cause of long-term disability. This calls for effective and accessible interventions to support participation in the community over time. One promising avenue to answer this need is telerehabilitation. Prior to conducting a larger trial, the main objective of this pilot study is to explore the feasibility, acceptability and preliminary efficacy of a meta-cognitive occupation-based intervention in a telerehabilitation format with adults and older adults in the chronic phase after ABI. Methods: Five community dwelling participants (ages 65-72), 6-10 months post ABI, with scores 2-4 on the modified Rankin scale and without dementia, completed the teleintervention. The intervention included approximately 10 weekly videoconferencing sessions administered by an occupational therapist using the Cognitive Orientation to Daily Occupational Performance approach. Each participant defined five functional goals, three were trained and two were not trained during the intervention. Evaluations were conducted at pre, post and 3-month follow-up. The primary outcome measures included activity performance (The Canadian Occupational Performance Measure; COPM), participation (the Mayo-Portland Adaptability Inventory-4 Participation Index; MPAI-4-P) and quality of life (QoL) (stroke impact scale; SIS). Other measures included a feedback interview, satisfaction questionnaire, field notes and a treatment fidelity checklist. Results: The teleintervention was found to be feasible and the participants expressed a high degree of satisfaction with the intervention and the technology use. A Wilcoxon Signed-Ranks test indicated statistically significant improvements post intervention in COPM performance (Z = -2.023, p=0.043) and satisfaction (Z = -2.023, p=0.043) ratings. Additionally, clinically significant improvements (≥2 points) in both performance and satisfaction with performance were found for each participant in at least three of their five defined functional goals. Trends toward significant improvement were found in MPAI-4-P ratings post intervention (Z = -1.826, p=0.068). Furthermore, clinically significant improvements (≥15 points) post intervention were found for each participant in some subscales of the SIS. Results were partially maintained at 3-month follow-up Conclusions: This pilot study demonstrated the feasibility of a metacognitive occupational-based telerehabilitation intervention, and its potential benefits in activity performance, participation and QoL for older adults coping with long-term disability following ABI. Trial Registration: ClinicalTrials.gov NCT02977624